Narratives of School Counselors Regarding Advocacy for LGBTQ Students. (January 2019) - Simons, Jack; Cuadrado, Mary
Using a directed form of qualitative research proposed by Mayring, this qualitative study applied Ajzen's Theory of Planned Behavior (TPB) to examine the efforts of nine self-identified school counselor advocates to advocate for lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ) students. This study is warranted because LGBTQ students commonly experience bullying in the absence of resources while also trying to navigate a new identity. Findings indicated that the work expectations of other school stakeholders, along with the school counselors' levels of advocacy self-efficacy and exposure to the LGBTQ community, were related to how, when, and why the school counselors advocated for LGBTQ students. We offer future research and practice recommendations to give more voice to LGBTQ students in the current sociopolitical climate.